2008
DOI: 10.1111/j.1464-5491.2007.02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between mean blood glucose and glycated haemoglobin in Type 2 diabetic patients

Abstract: Our results establish for the first time a strong correlation between MBG and HbA(1c) in Type 2 diabetic patients and support the idea of expressing HbA(1c) results as MBG. This will help patients to gain a clearer interpretation of the result, with less confusion. This simplification will allow every person with diabetes using home glucose-monitoring to understand his or her own target level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
3
14
0
2
Order By: Relevance
“…106 There have been other studies ( Table 2) that showed good correlation between MBG and HbA1c. 77,107,108 Makris and coworkers 107 reported results similar to that observed in the DCCT using patients with T2DM.…”
Section: Mathematical Relationship Between Hemoglobin A1c and Mean Blsupporting
confidence: 62%
“…106 There have been other studies ( Table 2) that showed good correlation between MBG and HbA1c. 77,107,108 Makris and coworkers 107 reported results similar to that observed in the DCCT using patients with T2DM.…”
Section: Mathematical Relationship Between Hemoglobin A1c and Mean Blsupporting
confidence: 62%
“…A utilização esporádica e não estruturada de testes de glicemia capilar não fornece os elementos necessários para a avaliação completa do estado glicêmico (23). Além do mais, a automonitorização é uma ferramenta prática para ajudar o paciente diabético a compreender melhor a sua doença e as metas do tratamento (24,25). Os pacientes incluídos neste estudo apresentavam ní-veis basais de controle glicêmico muito além do recomendado (A1C > 7%), portanto apresentavam um alto risco de desenvolver complicações micro e macrovasculares decorrentes do DM (2).…”
Section: Discussionunclassified
“…[19][20][21] Makris et al 21 observaram forte correlação entre HbA1C e GMS em pacientes com DM2. A HbA1C, entretanto, não é tão útil para indicar quais as mudanças na terapêutica farmacoló-gica ou nutricional seriam as mais adequadas, assim como não permite avaliar os resultados de tais alterações em curto prazo.…”
Section: Discussionunclassified